Ketamine and other glutamate receptor modulators for depression in adults with bipolar disorder - Dean, Rebecca L.; Marquardt, Tahnee; Hurducas, Claudia; Spyridi, Styliani; Barnes, Annabelle; Smith, Rebecca; Cowen, Philip J.; McShane, Rupert; Hawton, Keith; Malhi, Gin S.; Geddes, John; Cipriani, Andrea (My University, 2021)
Background: Glutamergic system dysfunction has been implicated in the pathophysiology of bipolar depression. This is an update of the 2015 Cochrane Review for the use of glutamate receptor modulators for depression in bipolar disorder. Objectives: 1. To assess the effects of ketamine and other glutamate receptor modulators in alleviating the acute symptoms of depression in people with bipolar disorder. 2. To review the acceptability of ketamine and other glutamate receptor modulators in people with bipolar disorder who are experiencing depressive symptoms. Search methods: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), Ovid MEDLINE, Embase and PsycINFO all years to July 2020. We did not apply any restrictions to date, language or publication status. Selection criteria: RCTs comparing ketamine or other glutamate receptor modulators with other active psychotropic drugs or saline placebo in adults with bipolar depression. Data collection and analysis: Two review authors independently selected studies for inclusion, assessed trial quality and extracted data. Primary outcomes were response rate and adverse events. Secondary outcomes included remission rate, depression severity change scores, suicidality, cognition, quality of life, and dropout rate. The GRADE framework was used to assess the certainty of the evidence. Main results: Ten studies (647 participants) were included in this review (an additional five studies compared to the 2015 review). There were no additional studies added to the comparisons identified in the 2015 Cochrane review on ketamine, memantine and cytidine versus placebo. However, three new comparisons were found: ketamine versus midazolam, N-acetylcysteine versus placebo, and riluzole versus placebo. The glutamate receptor modulators studied were ketamine (three trials), memantine (two), cytidine (one), N-acetylcysteine (three), and riluzole (one). Eight of these studies were placebo-controlled and two-armed. In seven trials the glutamate receptor modulators had been used as add-on drugs to mood stabilisers. Only one trial compared ketamine with an active comparator, midazolam. The treatment period ranged from a single intravenous administration (all ketamine studies), to repeated administration for riluzole, memantine, cytidine, and N-acetylcysteine (with a follow-up of eight weeks, 8 to 12 weeks, 12 weeks, and 16 to 20 weeks, respectively). Six of the studies included sites in the USA, one in Taiwan, one in Denmark, one in Australia, and in one study the location was unclear. All participants had a primary diagnosis of bipolar disorder and were experiencing an acute bipolar depressive episode, diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders fourth edition (IV) or fourth edition text revision (IV-TR). Among all glutamate receptor modulators included in this review, only ketamine appeared to be more efficacious than placebo 24 hours after infusion for response rate (odds ratio (OR) 11.61, 95% confidence interval (CI) 1.25 to 107.74; P = 0.03; participants = 33; studies = 2; I² = 0%, low-certainty evidence). Ketamine seemed to be more effective in reducing depression rating scale scores (MD -11.81, 95% CI -20.01 to -3.61; P = 0.005; participants = 32; studies = 2; I2 = 0%, very low-certainty evidence). There was no evidence of ketamine's efficacy in producing remission over placebo at 24 hours (OR 5.16, 95% CI 0.51 to 52.30; P = 0.72; participants = 33; studies = 2; I2 = 0%, very low-certainty evidence). Evidence on response, remission or depression rating scale scores between ketamine and midazolam was uncertain at 24 hours due to very low-certainty evidence (OR 3.20, 95% CI 0.23 to 45.19). In the one trial assessing ketamine and midazolam, there were no dropouts due to adverse effects or for any reason (very low-certainty evidence). Placebo may have been more effective than N-acetylcysteine in reducing depression rating scale scores at three months, although this was based on very low-certainty evidence (MD 1.28, 95% CI 0.24 to 2.31; participants = 58; studies = 2). Very uncertain evidence found no difference in response at three months (OR 0.82, 95% CI 0.32 to 2.14; participants = 69; studies = 2; very low-certainty evidence). No data were available for remission or acceptability. Extremely limited data were available for riluzole vs placebo, finding only very-low certainty evidence of no difference in dropout rates (OR 2.00, 95% CI 0.31 to 12.84; P = 0.46; participants = 19; studies = 1; I2 = 0%). Authors' conclusions: It is difficult to draw reliable conclusions from this review due to the certainty of the evidence being low to very low, and the relatively small amount of data usable for analysis in bipolar disorder, which is considerably less than the information available for unipolar depression. Nevertheless, we found uncertain evidence in favour of a single intravenous dose of ketamine (as add-on therapy to mood stabilisers) over placebo in terms of response rate up to 24 hours, however ketamine did not show any better efficacy for remission in bipolar depression. Even though ketamine has the potential to have a rapid and transient antidepressant effect, the efficacy of a single intravenous dose may be limited. We did not find conclusive evidence on adverse events with ketamine, and there was insufficient evidence to draw meaningful conclusions for the remaining glutamate receptor modulators. However, ketamine's psychotomimetic effects (such as delusions or delirium) may have compromised study blinding in some studies, and so we cannot rule out the potential bias introduced by inadequate blinding procedures. To draw more robust conclusions, further methodologically sound RCTs (with adequate blinding) are needed to explore different modes of administration of ketamine, and to study different methods of sustaining antidepressant response, such as repeated administrations.
Keywords: Acetylcysteine; Ionotropic receptor antagonist; Cytidine; Ketamine